Kritik terhadap Kapitalis-Patriakis dan Perspektif Subsistensi dalam Novel Aroma Karsa Karya Dewi Lestari - Rasiah Rasiah; Yana Yana; Faika Burhan (SASDAYA: Gadjah Mada Journal of Humanities, 2020)
Since capitalism-patriarchy is viewed as the specter of the problem of the emergence of injustice, it has been raising efforts to realize social justice and environmental sustainability through restructuring of the human mindset towards nature and fellow humans. The principle of capitalism-patriarchy has led to a culture of death and destruction because it is characterized by domination, power, exploitation, and environmental damage. This research sought to describe the criticism of patriarchal-capitalism and the subsistence perspective shown in the novel Aroma Karsa written by Dewi Lestari. Through ecofeminism proposed by Vandana Shiva and Mies, this study found that the power of the capitalist-patriarchal was represented through male figures such as; Jati Wesi, Khalil, and Ferdi, who utilize nature and parts of women's bodies for financial interests and sexual desires through the production of the most expensive perfume, make certain plant species endangered and oppressed. Their cultivation efforts cannot be separated from profit orientation. The perspective of subsistence is then carried out by women characters to preserve, protect, and utilize natural resources as needed out of exaggeration. It is illustrated through female figures; Janirah, Raras, and Tanaya Suma who tried to stem the power and domination of men over nature and women's bodies for the benefit of capital. The subsistence perspective in the novel Aroma Karsa by Dewi Lestari emphasizes the preservation and protection of nature for the sake of mutual needs and comfort, and it is women who understand more about nature more than men.